Health Risk And Criminal Behavior Among Substance Abuser In Malaysia A Narrative Review - Muhammad Farid Ahmad; Nazir Mohamad; Mohd Norbayusri Baharudin; Helmi Ibrahim (2024)
Objectives: This narrative review was done to summarize the findings of related research in the area of health risk and criminal behavior among substance abuser in Malaysia. This in depth review may lead to positive impact in enhancingthe knowledge of society on substance addiction. Another purpose of this review is to reduce the number of drug abusers which can lead to lower the numbers of health risk and criminal behavior, indirectly. Background: Health risk and criminal behavior is common among substance abuser. Theseare complex and interrelated problems that give effect significantly to the country. It creates a serious health challenges in Malaysia especially in rising number of overdose death, HIV and Hepatitis C infections. The link between health risk and criminal behavior among substance abusers also need to be highlighted. Methodology: The researchers searched selected articles which are related to health risk and criminal behavior among substance abuser in Malaysia through various search engines including Google, scholar and Ovid. Only the best 12articles were reviewed excluding case series, case report and reports. Research reviewed includes the relationship between health risk and criminal behavior among substance abuser in Malaysia that includes its definitions, epidemiology, genetics and issues of treatment center in Malaysia. Discussion: Types of health risks and criminal behavior among substance abuserare depends on their age, region, type of drug misuse and others. Most of the reviewed literatures suggest that there is significant association of health risk and criminal behavior with various substance abusers in Malaysia, which also happen in other countries. Conclusion: Further study is required to determine future consequences of health risk and criminal behavior among substance abuser in Malaysia.